Implementasi Kebijakan Tunjangan Profesi Guru Di Dinas Pendidikan Provinsi Jawa Timur - Andika, Alif Rizky; Pramudiana, Ika Devi (Soetomo Magister Ilmu Administrasi, 2023)
The purpose of this study is to find out how the policy of providing teacher professional allowances is implemented. This study also aims to determine the factors that support and hinder the implementation of policies related to the provision of teacher professional allowances at the East Java Provincial Education Office. In this study it was found that the implementation of the provision of teacher professional allowances with the perspective of Edward III narrowed down to four variables, namely communication, resources, disposition and bureaucratic structure. The teacher professional allowance is closely related to the teacher certification program. There are three important things in the implementation of teacher certification, namely preparation or planning for teacher certification before teaching, the process of implementing learning, and evaluation or assessment. The implementation of the teacher professional allowance policy has supporting factors and has an impact on its implementation for both teachers and schools, namely increased teaching motivation, more varied and creative teaching methods, increased teacher welfare, and increased teacher professionalism. The inhibiting factors in the implementation of the teacher professional allowance policy are the workload of teaching hours for teachers, the problem of social jealousy among teachers and the community, and the Teacher Professional Education program. Keywords: Implementation, Benefits, Profession, Teacher